Ibn Arabi's Veiw about the Role of Imagination in the Process of Perception - davoud esparham (حکمت و فلسفه, 2011)
Befor Inb Arabi, according to the Helenistic view, the human perception was confined to sensations and objects of reason. And, for the sensation was regarded as an instrument for reason, the latter was thought as the final perceptive faculty. Furthermore, the reason supported by logics, was regarded as the final judge. In the mentioned thought tradition, all of findings should be assessed in the light of reason to their truth of falsity be determined. Ibn Arabi suggests a new worldview and makes the traditional conception of reason encountered to some main challengs. According to this fact, orientalists rightly have called him the largest and most influential thinker in the second half of Islamic age. Ibn Arabi's meeting with Averoes – the main philosopher of his age – is regarded as a kind of end for a long time tradition and the begining of a new route. The route Ibn Arabi founded is takig authority from reason and giving it to the imagination in an strict sense. Nowaday, after the rise of postmodernism and many challenges about modern hypothses about the nature of human being and rationality, and refutation of many modern assumptions, inclination to reassessment of oriental thoughts has been increased, and therefore, there is an increasingly interest in Ibn Arabi's views. Thus, it is necessary to all of his ideas are studied in the light of current streams of thoughts. This paper tries to study and explicate Ibn Arabi's views about the imaginantion and its role and function in the realm of perception